2002
DOI: 10.1097/00000539-200207000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Small-Dose Ketamine Improves the Postoperative State of Depressed Patients

Abstract: NMDA receptor antagonists are reported to be effective for improving depression. It remains unclear whether ketamine, which is an NMDA receptor antagonist, postoperatively affects the psychological state in depressed patients. We investigated the effect of 1.0 mg/kg of ketamine on postoperative outcomes in depressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 19 publications
4
102
0
6
Order By: Relevance
“…Beside the abovementioned report on D-cycloserine, slight antidepressant effects in humans have also been observed with the NMDA receptor antagonists amantadine 10,11 and ketamine. 12,13 Riluzole, an antiglutamatergic agent believed to increase the glutamatergic uptake into the astrocytes, is under intensive investigation for its antidepressant potential. 14 A recent series of openlabelled studies and case reports demonstrated its efficacy.…”
Section: Glutamate In Depressionmentioning
confidence: 99%
“…Beside the abovementioned report on D-cycloserine, slight antidepressant effects in humans have also been observed with the NMDA receptor antagonists amantadine 10,11 and ketamine. 12,13 Riluzole, an antiglutamatergic agent believed to increase the glutamatergic uptake into the astrocytes, is under intensive investigation for its antidepressant potential. 14 A recent series of openlabelled studies and case reports demonstrated its efficacy.…”
Section: Glutamate In Depressionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31] Other than two case reports, [32][33][34] no studies to date have examined ketamine's role in treating depression or anxiety in the hospice population. To our knowledge, no investigations of depression treatment for any population have been carried out with oral ketamine, and only a couple investigations of ketamine have assessed symptoms of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 There is also a growing body of literature supporting the rapid treatment of depressive symptoms with intravenous (IV) ketamine. [15][16][17][18][19][20][21] A single case using IV ketamine to treat depression in a patient with advanced cancer has been reported. 22 No studies to date have examined ketamine's role in treating depression in the hospice population.…”
Section: Introductionmentioning
confidence: 99%